Early life cognitive function and health behaviours in late childhood: testing the neuroselection hypothesis. Issue 1 (9th November 2017) - Aggio, Daniel; Smith, Lee; Hamer, Mark
Abstract : Background: Higher cognitive function in childhood is associated with healthier behaviours and a reduced risk of chronic disease in adulthood, but it is unclear whether this selection of healthier behaviours occurs in childhood or later in life. The present study investigated how cognitive function at age 3–7 years was associated with health behaviours at age 11. Methods: Verbal, non-verbal and spatial abilities were assessed using the British Ability Scales at ages 3–7. At age 11, children reported how often they engaged in sport/physical activity, sedentary behaviours (eg, reading and games console usage), cigarette smoking and alcohol consumption. Logistic regression was used to estimate odds of engaging in health behaviours at age 11 according to early life cognition. Results: A 1 SD increase in early childhood verbal ability was associated with reduced odds of attempting smoking in boys and girls (OR 0.69 (95% CI 0.57 to 0.84)) and reduced odds of computer gaming in girls (OR 0.79 (95% CI 0.72 to 0.86)) by age 11. Early childhood verbal ability was also associated with reduced odds of regular participation in sport/active games (boys: OR 0.91 (95% CI 0.84 to 0.99); girls: OR 0.81 (95% CI 0.74 to 0.88)) and increased odds of reading for enjoyment (boys: OR 1.47 (95% CI 1.35 to 1.60); girls: OR 1.48 (95% CI 1.36 to 1.62)) at age 11. Early childhood non-verbal ability was associated with reduced odds of alcohol consumption in boys and girls (OR 0.92 (95% CI 0.85 to 0.99)) and reduced odds of online messaging in boys (OR 0.89 (95% CI 0.81 to 0.98)) at age 11. Early childhood spatial ability was associated with reduced odds of participating in sport/active games in boys at age 11 (OR 0.88 (95% CI 0.82 to 0.95). Conclusion: Neuroselection may occur during early childhood resulting in some, but not all, healthier behaviours by age 11.